Bell's palsy and HIV infection. Issue 3 (March 1988) - Brown, M M; Thompson, A; Goh, B T; Forster, G E; Swash, M
Abstract : Unilateral infranuclear facial palsy developed in three young homosexual men. All three were positive for antibodies to human immunodeficiency virus (HIV). Two had persistent generalised lymphadenopathy, but the clinical criteria for the acquired immune deficiency syndrome (AIDS) were not fulfilled. There were no features of generalised neuropathy, and no other cause for facial palsy was evident. Recovery was excellent in each patient.